Second Tripartite Technical Meeting for Hotels, Resturants and Similar Establishements Geneva, 1974 (International Labour Office, 1974)
Conditions of Work and Life of Migrant and Seasonal Workers Employed in Hotels, Restaurants and Similar Establishments